Disaggregated money supply and export competitiveness: A causal analysis using Tanzania's sectoral trade data - Enock Mwakalila; Lusekelo Kasongwa; Seif Muba (Social Sciences and Humanities Open)
Background: Export performance is crucial for Tanzania's macroeconomic development. However, the influence of different components of money supply on sectoral export competitiveness remains underexplored. Objectives: and Contributions: This study aims to investigate the short-term and long-term effects of disaggregated monetary aggregates (M1, M2, M3) on the performance of traditional, mining, and manufacturing exports in Tanzania. It contributes to the literature by offering sector-specific evidence on monetary transmission, a gap in existing macro-financial studies. Methods: Quarterly data from 2003 to 2024 were sourced from the Bank of Tanzania. The Autoregressive Distributed Lag (ARDL) approach was used to estimate both short-run dynamics and long-run relationships, supported by unit root, cointegration, and diagnostic tests. Results: M1 and M3 exhibit short-run negative associations with traditional exports, possibly reflecting inflationary and liquidity misallocation effects. M2 demonstrates a stronger long-run influence on manufacturing exports. Implications: These findings suggest that the impact of monetary policy differs by sector and aggregate type. Policymakers should adopt a more targeted approach in managing liquidity to avoid unintended distortions in trade performance.